Teaching material of the English language with specific ends for the students of medical sciences - Iris Caridad Hernández Barro (Centro Provincial de Información de Ciencias Médicas, 2021)
The motivation of elaborating a glossary of medical terms synonyms emerge due to the lack of support materials for the English language teaching with specific ends, in order to facilitate the translation, interpretation and communication of scientific-medical information for the health professionals, both in the national and foreign environment. Different works of the medical specialties and dictionaries were checked with this purpose; the final product consisted on a material denominated "Glossary of medical terms synonyms" whose validation was carried out through the comparison of the academic results, before and after its use, and the opinion of the teaching staff that used it.